Trends in cause-specific mortality among adults with and without diagnosed diabetes in the USA: an epidemiological analysis of linked national survey and vital statistics data. Issue 10138 (16th June 2018) - Gregg, Edward W; Cheng, Yiling J; Srinivasan, Meera; Lin, Ji; Geiss, Linda S; Albright, Ann L; Imperatore, Giuseppina
Summary: Background: Large reductions in diabetes complications have altered diabetes-related morbidity in the USA. It is unclear whether similar trends have occurred in causes of death. Methods: Using data from the National Health Interview Survey Linked Mortality files from 1985 to 2015, we estimated age-specific death rates and proportional mortality from all causes, vascular causes, cancers, and non-vascular, non-cancer causes among US adults by diabetes status. Findings: From 1988–94, to 2010–15, all-cause death rates declined by 20% every 10 years among US adults with diabetes (from 23·1 [95% CI 20·1–26·0] to 15·2 [14·6–15·8] per 1000 person-years), while death from vascular causes decreased 32% every 10 years (from 11·0 [9·2–12·2] to 5·2 [4·8–5·6] per 1000 person-years), deaths from cancers decreased 16% every 10 years (from 4·4 [3·2–5·5] to 3·0 [2·8–3·3] per 1000 person-years), and the rate of non-vascular, non-cancer deaths declined by 8% every 10 years (from 7·7 [6·3–9·2] to 7·1 [6·6–7·5]). Death rates also declined significantly among people without diagnosed diabetes for all four major mortality categories. However, the declines in death rates were significantly greater among people with diabetes for all-causes (pinteraction <0·0001), vascular causes (pinteraction =0·0214), and non-vascular, non-cancer causes (pinteration <0·0001), as differences in all-cause and vascular disease death between people with and without diabetes were reduced by about a half. Among people with diabetes, all-cause mortality rates declined most in men and adults aged 65–74 years of age, and there was no decline in death rates among adults aged 20–44 years. The different magnitude of changes in cause-specific mortality led to large changes in the proportional mortality. The proportion of total deaths among adults with diabetes from vascular causes declined from 47·8% (95% CI 38·9–58·8) in 1988–94 to 34·1% (31·4–37·1) in 2010–15; this decline was offset by large increases in the proportion of deaths from non-vascular, non-cancer causes, from 33·5% (26·7–42·1) to 46·5% (43·3–50·0). The proportion of deaths caused by cancer was relatively stable over time, ranging from 16% to 20%. Interpretation: Declining rates of vascular disease mortality are leading to a diversification of forms of diabetes-related mortality with implications for clinical management, prevention, and disease monitoring. Funding: None.